2018
DOI: 10.1152/ajpregu.00271.2017
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity, leptin, adiponectin, resistin, and testosterone in adult male and female rats after maternal-neonatal separation and environmental stress

Abstract: Care of premature infants often requires parental and caregiver separation, particularly during hypoxic and hypothermic episodes. We have established a neonatal rat model of human prematurity involving maternal-neonatal separation and hypoxia with spontaneous hypothermia prevented by external heat. Adults previously exposed to these neonatal stressors show a sex difference in the insulin and glucose response to arginine stimulation suggesting a state of insulin resistance. The current study used this cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Interestingly, acute hypoxia did not stimulate neonatal testosterone production which does not agree with previous studies (Boksa & Zhang, 2008;Liu & Du, 2002). One possible explanation for this is the prior use of relatively nonspecific immunoassays for testosterone whereas we used a more specific and sophisticated LC-MS/MS method validated for the use in rat plasma (Raff et al, 2018). Regardless, we showed that flutamide has effects in the nonstressed male neonate confirming that an increase in testosterone is not required to exert important physiological effects (Gray et al, 2006;McCormick, Furey, Child, Sawyer, & Donohue, 1998…”
Section: Sexual Dimorphismmentioning
confidence: 72%
See 2 more Smart Citations
“…Interestingly, acute hypoxia did not stimulate neonatal testosterone production which does not agree with previous studies (Boksa & Zhang, 2008;Liu & Du, 2002). One possible explanation for this is the prior use of relatively nonspecific immunoassays for testosterone whereas we used a more specific and sophisticated LC-MS/MS method validated for the use in rat plasma (Raff et al, 2018). Regardless, we showed that flutamide has effects in the nonstressed male neonate confirming that an increase in testosterone is not required to exert important physiological effects (Gray et al, 2006;McCormick, Furey, Child, Sawyer, & Donohue, 1998…”
Section: Sexual Dimorphismmentioning
confidence: 72%
“…The main motivation for this study was our previous findings that neonatal stressors program the control of HPA axis, insulin and glucose, and other metabolic biomarkers in the adult rat in a sexually dimorphic manner (Gehrand et al, 2018(Gehrand et al, , 2016Raff et al, 2018). Based on the literature, we thought that stress-induced testosterone responses in the neonatal male rat could be responsible for this longterm programming (Boksa & Zhang, 2008;Brunton, 2015;Clarkson & Herbison, 2016;Jopek et al, 2017;Kasprzak & Lesniewska, 1986;Liu & Du, 2002;Slob, Ooms, & Vreeburg, 1980;Vega Matuszczyk, Silverin, & Larsson, 1990;Ward, Ward, Denning, French, & Hendricks, 2002).…”
Section: F I G U R E 4 Femalementioning
confidence: 99%
See 1 more Smart Citation
“…An HFC feeding increased serum insulin concentration in MS males but reduced that of corticosterone, consistent with previous data (5). MS-induced insulinemia is prevented by mechanical and tactical stimulation of the pups (56), supporting the role of neonatal stress shown to alter the pancreatic beta-cell function and insulin sensitivity in rats, with males being more sensitive than females (58, 59).…”
Section: Discussionmentioning
confidence: 71%
“…This result agreed with previous studies examining maternal separation on rats during PND2–9 or PND10–17 [ 39 ]. Some previous studies showed that repeated maternal separation altered body weight in offspring [ 40 , 41 ], which may be related to variation of MS protocol (longer versus shorter time separation), species of animals, or the different postnatal periods of MS [ 42 ]. Moreover, EA stimulation in young adulthood does not affect the weight gain of rats with MS, compared to the MS or control group ( Figure 1(b) ).…”
Section: Discussionmentioning
confidence: 99%